Applications of Strategic Management Practices in Public Sector: Cases From Some Middle East Countries - Tamimi, Saleh Abdelhamid (Advances in Social Sciences Research Journal, 2018)
Abstract The aim of this research paper is to investigate Strategic Management (SM) practice in Public Organizations (POs) within some Middle East (MEt) countries. This is an archival-desktop research paper reviewing available literature on SM in the last two decades. Fundamentally, this paper posts a question of; “How do POs in MEt countries practice SM?” The answer of this investigation is being based on the extent of the available literature from SM theory and application within public sector in some MEt countries. This paper is one of the first attempts to analysis and interpret SM practices within MEt region. This analysis used content analyses techniques, the researcher found four variables that contribute in the effectiveness of SM existence conditions within POs. These variables are; public reform, and SM elements (strategy formulation, implementation, and evaluation) situations and challenges. Finally, this paper discussed the implication and lessons learned for improvement. Findings indicate that even though there are some countries practice SM in this area in various degrees, but it also shows that most of these countries are struggling in practicing SM for various reasons. While, results showed a positive impact of SM tools practices on POs performance. Outcomes also indicate that there are other issues needs to be considered in these countries which are public-reforms and decentralization successes within POs in each case. However, relying on data from literature review limits the in-depth discussion but at least offer critical analysis on achievements of SM implementation in MEt countries.